2007
DOI: 10.1074/jbc.m701985200
|View full text |Cite
|
Sign up to set email alerts
|

Role of a Carboxylesterase in Herbicide Bioactivation in Arabidopsis thaliana

Abstract: Arabidopsis thaliana contains multiple carboxyesterases (AtCXEs) with activities toward xenobiotics, including herbicide esters that are activated to their phytotoxic acids upon hydrolysis. On the basis of their susceptibility to inhibition by organophosphates, these AtCXEs are all serine hydrolases. Using a trifunctional probe bearing a fluorophosphonate together with biotin and rhodamine to facilitate detection and recovery, four dominant serine hydrolases were identified in the proteome of Arabidopsis. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
42
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 32 publications
2
42
0
Order By: Relevance
“…So far, serine hydrolase profiling in plants was limited to a single study where four FP-labeled enzymes were identified from Arabidopsis leaf extracts. These labeled proteins were prolyl oligopeptidase At1g76140, carboxypeptidase CXE12 (At3g48690), serine hydrolase At5g20060, and a GDSL lipase (13). In this study, we used multidimensional protein identification technology (MudPIT) and in-gel digestions to identify over 50 serine hydrolase activities in Arabidopsis leaf extracts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…So far, serine hydrolase profiling in plants was limited to a single study where four FP-labeled enzymes were identified from Arabidopsis leaf extracts. These labeled proteins were prolyl oligopeptidase At1g76140, carboxypeptidase CXE12 (At3g48690), serine hydrolase At5g20060, and a GDSL lipase (13). In this study, we used multidimensional protein identification technology (MudPIT) and in-gel digestions to identify over 50 serine hydrolase activities in Arabidopsis leaf extracts.…”
mentioning
confidence: 99%
“…Carboxypeptidase-like SNG1, for example, acts as an acyltransferase in the production of sinapoylmalate (11), and some GDSL lipase-like proteins act as sinapine esterases (12). Furthermore carboxylesterase-like CXE12 activates herbicides by hydrolysis (13), and several methylesterases hydrolyze methylated phytohormones like salicylic acid, jasmonic acid, and indoleacetic acid (14).…”
mentioning
confidence: 99%
“…These compounds act as "proauxins," which diffuse efficiently to the tissue, where they undergo cleavage and release functional auxins. 14,15 Our results suggested that 2,4-D IOE might permeate efficiently into the tissue and release active 2,4-D, which promotes xylem vessel differentiation through SCF TIR1/ AFB auxin signaling pathway. 13 To confirm this idea, we analyzed the effect of a bipartite pro-auxin named 533, 14 on xylem vessel differentiation in the acl5 mutant (Fig.…”
Section: Thermospermine Suppresses Auxin-inducible Xylem Differentiatmentioning
confidence: 95%
“…Plant esterases (EC 3.1.1.X) are a kind of esterases of soybeans, wheat, sorghum, rice and other species [6,10,11]. They catalyze the conversion of carboxylic esters to bioactive acids and alcohols, thus playing a key role in many biological processes, such as the activation of signaling molecules [12] and the regulation of the bioactivity of endogenous products [13], including hydrolytic cleavage of ester bonds in pesticides and other xenobiotics [6].…”
mentioning
confidence: 99%
“…The aim of this study was to estimate the isoenzyme profile of esterases isolated from mature seeds, and to ascertain, using such a biochemical marker, the polymorphism among samples of promising breeding material of the hexaploid wheat (Triticum aestivum L.). Ripe seeds from following wheat cultivars were used as samples: Zlata, Lyubava, Agatha, Lisa (spring wheat) and Mera (winter wheat) (originated by Moscow Agricultural Research Institute «Nemchinovka», Moscow Province); lines AFI91 and AFI177 (spring wheat) and recombinant inbred lines of the mapping populations 10,29, 32, 44, 47, 57, 83, 88, 89, and 115 (spring wheat) (originated by Agrophysical Research Institute -AFI, St. Petersburg). The seeds were ground in a porcelain mortar and the flour was sieved.…”
mentioning
confidence: 99%